Revolutionary Road: Collective Analysis of a Literary Text - Spaziante , Lucio (E|C, 2023)
The paper deals with a semiotic analysis of the literary text, focusing on Richard Yates’ novel Revolutionary Road (1961): a dramatic mid-twentieth-century portrait of social appearances and their negative impact on personal identities. The analysis was carried out by a group of students as part of a seminar at the University of Bologna, in the master’s degree program in Semiotics, and constitutes the outcome of an experiment that led to a research product through a didactic process. In the first phase, the novel was analyzed in each individual chapter; then, through didactic coordination, a few macro-themes (spatiality , temporality, corporeity, gender) emerged which the subgroups proceeded to a specific in-depth study. Among the results, it appeared how spatiality is a relevant feature not in itself, but in relation to the sense effects it produces: such as the opposition between public and private , and the relationship between social appearances and intimate dimensions. The temporal dimension was also considered relevant: a back-and-forth between past and future related to the characters’ nostalgia for a future they never realized. Finally, the analysis showed the relevance, within the novel, of the correlation between corporeality , gender and passions , not only functional to describe the characters, but to define their status as social bodies, which in the fictional story possessed a higher value than natural bodies.